2015
DOI: 10.15809/irriga.2015v20n3p587
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade Industrial De Grãos De Arroz Decorrente Da Supressão Da Irrigação E Umidade De Colheita

Abstract: QUALIDADE INDUSTRIAL DE GRÃOS DE ARROZ DECORRENTE DA SUPRESSÃO DA IRRIGAÇÃO E UMIDADE DE COLHEITA  GUILHERME PILAR LONDERO¹; ENIO MARCHESAN²; EVANDRO PARISOTTO³; LUCAS LOPES COELHO4, BRUNO BEHENCK ARAMBURU4; CAMILLE SOARES FLORES4 E ANELISE LENCINA DA SILVA4 1 Mestrando do Programa de Pós-Graduação em Agronomia, Universidade Federal de Santa Maria, Av. Roraima nº 1000, 97105-900, Santa Maria/RS, e-mail: guilhermelondero@msn.com;2 Professor Titular do Departamento de Fitotecnia, Universidade Federal de Santa Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…O calor favorece a formação de gesso devido ao acúmulo irregular e pouco compactado dos fotoassimilados no endosperma. Consequentemente, os grãos ficam mais frágeis durante o processamento industrial, aumentando a quebra e diminuindo o rendimento de engenho (ALI et al, 2019;LYMAN et al, 2013;LONDERO et al, 2015;SREENIVA-SULU et al, 2015;ZHAO & FITZGERALD, 2013).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…O calor favorece a formação de gesso devido ao acúmulo irregular e pouco compactado dos fotoassimilados no endosperma. Consequentemente, os grãos ficam mais frágeis durante o processamento industrial, aumentando a quebra e diminuindo o rendimento de engenho (ALI et al, 2019;LYMAN et al, 2013;LONDERO et al, 2015;SREENIVA-SULU et al, 2015;ZHAO & FITZGERALD, 2013).…”
Section: Resultsunclassified
“…De modo geral, os resultados obtidos comprovam as observações feitas por Beckles & Thitisaksakul (2013) e Londero et al (2015), de que a aparência do grão de arroz é prejudicada pela elevação da temperatura durante o desenvolvimento do grão. Segundo Lyman et al (2013), o aumento da temperatura durante o enchimento de grãos fomenta a quebra e o gesso dos grãos e reduz a produtividade.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A similar result was found in 2011/2012 but not in 2014/2015 in our sample. Londero et al (2015) reported that the water deficits after anthesis did not change the quality of grains of irrigated rice. Therefore, this characteristic explains the difference between the agricultural years caused by the different distribution of rainfall , which contributed to the maintenance of grain quality regardless of the sprinkler irrigation depth adopted in 2014/2015.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that works on the effects of the association between N, Si, and fungicide applications on the industrial quality of irrigated rice grains are still scarce. Some studies have related grain quality to factors such as different humidity levels and fungicide use (Teló et al, 2011), irrigation suppression (Londero et al, 2015), high temperature (Nakata et al, 2017), and shading (Deng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%